FORMING OF DISCIPLINE CULTURE IN MADRASAH QUR’AN ISLAMIC BOARDING SCHOOL, SABAK AUH DISTRICT, SIAK REGENCY, RIAU PROVINCE - filda sandora; rini setyaningsih (Jurnal Ilmiah Pesantren, 2022)
The purpose of this research is to find out how the form of discipline in the Islamic boarding school madrasatul Qur’an and how the strategy in the formation of a culture of discipline in the Islamic boarding school Madrasatul Qur’an. This study used a qualitative research method with research subjects, namely the head of the boarding school as the key informant and the student staff and stakeholders as additional informants. Research data obtained through observation, interview and documentation techniques. The technique of checking the validity of the research data was triangulation. Data analysis used is data collection, data reduction, data presentation and drawing conclusions. The results of the research that the researchers obtained in the formation of a disciplined culture at the Madrasatul Qur’an Islamic Boarding School were. 1) the leadership of the boarding school and internal organizations form discipline, namely by arranging activities in a systematic and directed manner, so that it is easy to control. 2) The strategy used in the formation of a culture of discipline is more effectively used, namely through moral education, exemplary leadership of the boarding school. Then, the intensity of the continuous interaction between the students and the board. There are rules and sanctions for students that are used to establish a disciplinary culture for students. To carry out these two things, the leader has an important role ini carrying out his duties and fuctions. Leaders must make subordinates aware of their duties and responsibilitional goals. In this case the leader must have the abality to manage an educational institution